Sex identification of morphologically‐undifferentiated Siberian sturgeon with statistical analysis of gene expression patterns. (26th September 2021) - Lasalle, André; Norbis, Walter; Vizziano‐Cantonnet, Denise
Abstract: The purpose of this study was to detail a simple strategy for sexing morphologically‐undifferentiated fish using statistical analysis of gene expression patterns characterized by quantitative PCR. This approach is especially relevant for species without known genomic sex markers. The method was developed for early identification of female Siberian sturgeon as part of a genomics study. That study documented activation of the enzyme 17ß ‐ hydroxy ‐ steroid ‐ dehydrogenase ( hsd17b1 ) in future ovarian tissue at 3 months of age, concurrent with a small forkhead box L2 ( foxl2 ) peak and emerging cytochrome P450, family 19, subfamily A ( cyp19a1 ) expression. Major cyp19a1 and foxl2 peaks occurred in presumptive female gonads at 5–6 months. This pattern suggested a genetic relay mediating estrogen production throughout differentiation, possibly to maintain gonadal femininity. Genes involved in stem cell proliferation ( lim homeobox 2 ( lhx2 )) and somatic‐germ cell interaction maintenance ( iroquois homeobox 5 ( irx5 ) and iroquois homeobox 3 ( irx3 )) were also expressed during molecular differentiation, at 5–6 months. The roles of lhx2, irx3, and irx5 in fish sex differentiation should be confirmed using other methodologies. These results indicate that estrogens are crucial for ovarian differentiation in basal non‐teleost fish, consistent with well‐established patterns in teleosts, with hsd17b1 as one of the earliest biomarkers of gonadal development.